2019
DOI: 10.1103/physrevlett.123.137201
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Symmetry on Anisotropic Magnetoresistance in Textured Ferromagnetic Thin Films

Abstract: We report on the magnetoresistance of textured films consisting of 3d-ferromagnetic layers sandwiched by Pt. While the conventional cos 2 φ behavior of the anisotropic magnetoresistance (AMR) is found when the magnetization M is varied in the film plane, cos 2n θ contributions (2n ≤ 6) exist for rotating M in the plane perpendicular to the current. This finding is explained by the symmetry-adapted modeling of AMR of textured films demonstrating that the cos 2 θ behavior cannot be used as a fingerprint for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 75 publications
0
21
0
Order By: Relevance
“…The difference between the two estimated values may be ascribed to the ambiguity of fitting parameters such as P and λCo. In addition, other mechanisms including anomalous SMR which was reported in the Pt / Co bilayers [67] and anisotropic magnetoresistance in textured FM films [68], may also contribute to the observed SMR signal. Considering these points, we conclude that the present Cu95Ir5 possesses a relatively large θSH and a short λSD.…”
Section: Harmonic Hall Voltage Measurementsmentioning
confidence: 80%
“…The difference between the two estimated values may be ascribed to the ambiguity of fitting parameters such as P and λCo. In addition, other mechanisms including anomalous SMR which was reported in the Pt / Co bilayers [67] and anisotropic magnetoresistance in textured FM films [68], may also contribute to the observed SMR signal. Considering these points, we conclude that the present Cu95Ir5 possesses a relatively large θSH and a short λSD.…”
Section: Harmonic Hall Voltage Measurementsmentioning
confidence: 80%
“…72 There also exist several similar spindependent MR effects in SH/FM all-metallic heterostructures, such as the sizable SMR in samples with PMA 70,73 and unidirectional SMR (USMR) in samples with in-plane magnetic anisotropy. 74 However, the existence of the texture-dependent anisotropic interfacial magnetoresistance (AIMR) also needs to be carefully considered for a reasonable estimation of the SMR, as recently suggested by Philippi-Kobs et al 75…”
Section: Spin Hall Magnetoresistancementioning
confidence: 99%
“…The above equations are only valid for polycrystalline HM layers as it is the case for the standard Pt/YIG//YAG bilayer samples. For crystalline materials, the symmetry of the crystal has to be taken into account for the calculation of the resistivity tensor ρ [95][96][97]. For the inverted YIG/Pt//YAG bilayer sample types, we found that the Pt layer is weakly textured along the [111]-direction [see Fig.…”
Section: Magnetotransport Measurementsmentioning
confidence: 99%